2013
DOI: 10.1007/s13312-013-0234-6
|View full text |Cite
|
Sign up to set email alerts
|

Cost of neonatal intensive care delivered through district level public hospitals in India

Abstract: Level II neonatal intensive care at SCNUs is cost intensive. Rational use of SCNU services by targeting its utilization for the very low birth weight neonates and maintenance of community based home-based newborn care is required. Further research is required on cost-effectiveness of level II neonatal intensive care against routine pediatric ward care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 15 publications
3
48
0
Order By: Relevance
“…No cost-effectiveness studies were identified on the Integrated Management of Neonatal and Child Illness (IMNCI) or integrated community case management. Prinja and others (2013) note that even though overall health expenditures per case did not increase as IMNCI was implemented, there was an increase from the perspective of the government, which they estimate to be 1 percent to 1.5 percent of the government's health budget (US$0.61 to US$2.60 per child covered), depending on which field workers implement the program. The additional costs arose because the program was effective, which led to increased utilization as households switched from using private health providers.…”
Section: Platforms For Delivery Of Interventionsmentioning
confidence: 99%
“…No cost-effectiveness studies were identified on the Integrated Management of Neonatal and Child Illness (IMNCI) or integrated community case management. Prinja and others (2013) note that even though overall health expenditures per case did not increase as IMNCI was implemented, there was an increase from the perspective of the government, which they estimate to be 1 percent to 1.5 percent of the government's health budget (US$0.61 to US$2.60 per child covered), depending on which field workers implement the program. The additional costs arose because the program was effective, which led to increased utilization as households switched from using private health providers.…”
Section: Platforms For Delivery Of Interventionsmentioning
confidence: 99%
“…[5] The admission of ELBW babies to the NICU remains controversial in poorly resourced settings because of the high associated morbidity, mortality and cost of care. [6,7] There is limited information about the outcome of ELBW babies in developing countries, including South Africa (SA), and what is known is restricted to larger or academic hospitals. Previous SA studies have tended to consider the outcome of babies with a very low birth weight, rather than ELBW babies.…”
Section: Articlementioning
confidence: 99%
“…The cost of establishing a neonatal intensive care unit runs into cores of rupees in India in which equipment cost formed two-thirds of the establishment cost and ancillary personnel salary comprised the largest proportion of the running costs [7]. Neonatal intensive care is cost intensive and rational use of neonatal unit services by targeting its utilization for the very low birth weight neonates and maintenance of community based home-based newborn care is required [8]. High neonatal mortality rate in a country reflects the poor availability of quality and quantity of infrastructure and utilization of neonatal care of that country.…”
Section: Introductionmentioning
confidence: 99%